The Study of Development of Urban Farming Agrotourism Subak-Irrigation-Based in Sanur Tourism Area, Denpasar City, Bali - Sardiana, I Ketut (Graduate School, Universitas Brawijaya, 2018)
This study aims to study the development of urban farming agrotourism planning in Sanur Tourism area. The approach used is the Participatory Rural Appraisal (PRA), which is an approach that combines knowledge and opinions of rural communities in the planning and management of development programs. Data obtained through field observation, Focus Group Discussion (FGD) and in-depth interviews involving all stakeholders in the development of agro-tourism Sanur. The study shows that the development of agrotourism aimed at two central points of development, namely: Subak Sanur in Sanur Kaja, with wide appeal in the form of farmers markets, urban farming field schools, and layout biocircle farming; and Subak Intaran Kauh and Intaran Kangin in Village of Sanur Kauh and Sanur Kaja, with wide appeal among others cycling in paddy fields, education agrarian culture and irrigation systems Subak, attractions farming, social-religion activities, recreational fishing and bird watching. Development of facilities including the construction of gates and parking areas, information service facilities, toilets and bicycle parking, and a viewing post/gazebo, as well as cycling paths. Accessibility and circulation path aimed at structuring the Subak as cycling paths and setting its utilization by residents of Subak. Institutional development is directed to revitalization and empowerment of existing traditional institutions, through improvement of managerial capacity, prepare awig awig (written rules), and increasing the knowledge and skills of people in the process of adding value agricultural commodities. Keywords: development, agrotourism, urban farming, Subak-irrigation based